IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM ANAK USIA DINI DI RA ROUDHOTUL QURRO TANJUNGBALAI - Syamsu Nahar; Yusnaili Budianti; Rabiatul Adawiyah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2021)
The implementation of early childhood Islamic education learning at RA Raudhatul Qurro Tanjungbalai is carried out in the form of role playing, and the learning uses story methods, playing methods, singing methods, drawing methods to exemplary methods.This study uses a qualitative method. This data collection technique uses interview, observation and documentation techniques, the data analysis technique uses data reduction, data display and conclusion drawing. The results of this study indicate that; (1) Planning for early childhood Islamic Religious Education learning at Raudhatul Athfal Raudhatul Qurro, namely mastering the memorization of juz 'amma, increasing dexterity in worship practices, being able to sing about the blessings of the Prophet Muhammad. Practicing how to call to prayer at dawn with the call to prayer for Maghrib, design the values of uswatun hasanah, such as educating them (early children of RA Raudhatul Qurro). (2) The implementation consists of two, namely the implementation in the form of methods and materials (3) The evaluation is a daily evaluation in the form of diagnostic tests, formative evaluations and summative evaluations based on their implementation to measure learning outcomes (4) The inhibiting factor is the teacher who teaches at Raudhatul Athfal Raudhatul Qurro Tanjungbalai is 79% and comes from a bachelor's degree in education but not specifically in the field of PGRA or PGMl while the supporting factors are; The existence of the carrying capacity of the learning curriculum that is in line with the talents and interests of early childhood and the Tanjungbalai city government and the Tanjungbalai City ministry of religion support